Menggonyoh Sogel : During the Pause From Rice Threshing - Hakimi, Halim (Unit Penerbitan UiTM Perak, 2025, 2025)
HALIMThis photographic work captures a poignant moment at the humapaddy terrace in Kampung Semban, Kota Padawan. The imagepresents three subjects including the Famous Sarawak Ring Ladies,adorned with traditional ring taking a break from work. Inspontaneous moment, the three subjects are seen simultaneouslychewing sogel— a blend of tobacco and betel nut—a practice deeplyrooted in their cultural heritage and smoking traditional cigarette.Inspired by the concept of the “Decisive Moment” as pioneered byHenri Cartier- Bresson, the father of modern photojournalism, thisphotograph transcends mere documentation. The unplanned andunposed synchronization of the subject’s actions—each bringingsomething to their mouths—captures an ephemeral slice of life thatspeaks to the shared experiences and rhythms of daily existence inthis remote village.